Study on wave setup with the storm surge in Hai Phong coastal and estuarine region - Hien, Nguyen Xuan; Uu, Dinh Van; Thuc, Tran; Tien, Pham Van (VNU Journal of Science: Earth and Environmental Sciences; Vol 26 No 2, 2010)
Abstract. Wave setup is the increase of water level within the surf zone due to the transfer of wave-related momentum to the water column during wave-breaking. Wave setup contributes to the total water height in storm and become dangerous to coastal construction. This study presents some results on wave setup with storm surge using numerical model and empirical model. It also estimates the contribution of wave setup in total storm tide level at coastal and estuarine region of Hai Phong. Results show that wave setup at coastal and estuarine region in Hai Phong contributes about 25% to 40% of sea level surge in storm, 32% on average. Keywords: wave setup, storm surge, Hai Phong.